2021
DOI: 10.1016/j.redox.2021.101962
|View full text |Cite
|
Sign up to set email alerts
|

AQP8 is a crucial H2O2 transporter in insulin-producing RINm5F cells

Abstract: Peroxiporins are distinct aquaporins (AQP) which, beside water, also facilitate the bidirectional transport of hydrogen peroxide (H 2 O 2 ) across cellular membranes. H 2 O 2 serves as the major reactive oxygen species that mediates essential cell signaling events. In pancreatic β-cells, H 2 O 2 has been associated with the regulation of cell growth but in excess it leads to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…Having established COMPARE IT, we next sought to visualize H 2 O 2 uptake and its diffusion in endothelial cells into cell compartments in direct comparison among neighboring cells. Former studies emphasize that the stable reactive oxygen species (ROS) H 2 O 2 can readily diffuse into cells [ 26 , 27 ] to modulate diverse redox-sensitive proteins and cell functions, thus serving as an essential signaling molecule [ 28 ]. Several studies suggest that different aquaporin isoforms facilitate H 2 O 2 diffusion across the plasma membrane and intracellular membranes of cellular organelles [ 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Having established COMPARE IT, we next sought to visualize H 2 O 2 uptake and its diffusion in endothelial cells into cell compartments in direct comparison among neighboring cells. Former studies emphasize that the stable reactive oxygen species (ROS) H 2 O 2 can readily diffuse into cells [ 26 , 27 ] to modulate diverse redox-sensitive proteins and cell functions, thus serving as an essential signaling molecule [ 28 ]. Several studies suggest that different aquaporin isoforms facilitate H 2 O 2 diffusion across the plasma membrane and intracellular membranes of cellular organelles [ 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…AQP8 in the inner mitochondrial membrane was shown to confer Hg 2+ -sensitive water permeability in liver cell mitochondria [540]. In a pancreatic β-cell line, excess H 2 O 2 was linked to a failure of insulin release, potentially significant for diabetes; increased levels of AQP8 had a protective effect, proposed to result from the AQP8-mediated fluxes of H 2 O 2 across mitochondrial and plasma membranes [541]. AQP8 in the inner mitochondrial membrane of renal proximal cells increases as an adaptive response to acidosis, allowing the excretion of ammonia [542].…”
Section: Control Of Aqp Trafficking and Subcellular Localizationmentioning
confidence: 99%
“…The upregulation of Srxn1 has been shown to increase the survival of cardiac progenitor cells and astrocytes by protecting them against oxidative stress ( Li et al, 2018 ; Zhou et al, 2015 ). Aqp8 expression is a marker of mitochondrial function ( Ikaga et al, 2015 ), and has been shown to be protective by transporting H 2 O 2 out of pancreatic cells in the context of diabetes mellitus ( Krüger et al, 2021 ). The downregulation of Aqp8 in Ercc1 Δ/− hearts would lead to increased oxidative stress and mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%